2015
DOI: 10.1124/mol.114.096602
|View full text |Cite
|
Sign up to set email alerts
|

Mis-Trafficking of Endosomal Urokinase Proteins Triggers Drug-Induced Glioma Nonapoptotic Cell Death

Abstract: 5-Benzylglycinyl-amiloride (UCD38B) is the parent molecule of a class of anticancer small molecules that kill proliferative and nonproliferative high-grade glioma cells by programmed necrosis. UCD38B intracellularly triggers endocytosis, causing 40-50% of endosomes containing proteins of the urokinase plasminogen activator system (uPAS) to relocate to perinuclear mitochondrial regions. Endosomal "mis-trafficking" caused by UCD38B in human glioma cells corresponds to mitochondrial depolarization with the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 37 publications
5
23
0
4
Order By: Relevance
“…We focused on mitochondria, which act as the control unit of the cell being involved in the cell response to a wide range of insults [34], showing that in HMA-treated colon cancer cells they appeared to be relocalised to the perinuclear region (as recently reported in breast cancer cells [9]) and functionally impaired due to mitochondrial membrane depolarization. This is in agreement with the observations obtained in erythroleukemia cells treated with 5-(N-ethyl-N-isopropyl) amiloride [35] and in glioma cells with 5-benzylglycinyl-amiloride [36] and with the well-known inhibition of mitochondrial complex I activity by amilorides [37]. …”
Section: Discussionsupporting
confidence: 92%
“…We focused on mitochondria, which act as the control unit of the cell being involved in the cell response to a wide range of insults [34], showing that in HMA-treated colon cancer cells they appeared to be relocalised to the perinuclear region (as recently reported in breast cancer cells [9]) and functionally impaired due to mitochondrial membrane depolarization. This is in agreement with the observations obtained in erythroleukemia cells treated with 5-(N-ethyl-N-isopropyl) amiloride [35] and in glioma cells with 5-benzylglycinyl-amiloride [36] and with the well-known inhibition of mitochondrial complex I activity by amilorides [37]. …”
Section: Discussionsupporting
confidence: 92%
“…While some have identified specific perturbations in cell cycle progression and DNA integrity [35], the majority of studies have focused on plasma membrane associated ion and proton transporters [11,12,41], and/or uPA as the therapeutic targets (reviewed in [11]). Along these lines, a recent study suggested that UCD38B-induced necrosis depends upon mis-trafficking of endocytosed uPAR [15]. Specifically, the aberrant perinuclear accumulation of uPAR containing endosomes in close proximity to mitochondria may induce mitochondrial membrane depolarization and release of the pro-death factor AIF [15].…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, a recent study suggested that UCD38B-induced necrosis depends upon mis-trafficking of endocytosed uPAR [15]. Specifically, the aberrant perinuclear accumulation of uPAR containing endosomes in close proximity to mitochondria may induce mitochondrial membrane depolarization and release of the pro-death factor AIF [15]. While our data support mitochondrial dysfunction in mediating HMA associated cell death, evidenced by increased mitochondrial swelling, aggregation and ROS production, it is probable that endosomal trafficking may only be a consequence of amiloride derivative action and not required for cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one example, the vacuole-inducing anti-cancer compound, 5-benzylglycinyl-amiloride, has been reported to cause necrotic cell death in glioblastoma cells by redirecting endosomes containing the LRP-1 receptor and its associated urokinase plasminogen activator system to perinuclear mitochondrial regions, where release of mitochondrial AIF (apoptosis-inducing factor) is triggered (Pasupuleti et al 2015). In another study, leelamine, a tricyclic diterpene that induces caspase-independent death in melanoma cells, was shown to impair endosomal trafficking and autophagic flux, with consequent accumulation of cholesterol in endosomal compartments and disruption of multiple pro-survival receptor tyrosine kinase signaling pathways (Kuzu et al 2014).…”
Section: Discussionmentioning
confidence: 99%